Pengaruh Intimate Partner Violence terhadap Suicide Ideation pada Perempuan Korban - Athaya Nabilah Irawan; Suhana (Jurnal Riset Psikologi, 2024)
Abstract. Violence against women in romantic relationships in Indonesia in 2021 reported to Komnas Perempuan was 2,047 cases out of a total of 2,527 cases. This study aims to explain the effect of IPV on suicide ideation in women victims of violence. Intimate partner violence (IPV) is any form of violence that occurs in romantic relationships due to unresolved conflicts in the relationship. Suicide ideation is the thoughts that exist in individuals about death and other people's responses to them when they are no longer in the world. This study is a causal research with a quantitative approach involving 81 women as respondents. This study uses two measuring instruments The Revised Conflict Tactics Scales 2 (CTS2) which has been adapted by Zahra (2017) and the Adult Suicide Ideation Questionnaire (ASIQ) which has been adapted by Astuti (2019). The analysis used is simple linear regression. The regression coefficient value is positive 0.421, which means that if there is an increase in the IPV variable, there will be an increase in suicide ideation. The value of t count> t table or 5.214> 1.667 means that there is a significant influence between IPV and Suicide Ideation. Abstrak. Kekerasan terhadap perempuan dalam hubungan romantis di Indonesia pada tahun 2021 yang dilaporkan kepada Komnas Perempuan sebanyak 2,047 kasus dari jumlah keseluruhan 2,527 kasus. Penelitian ini memiliki tujuan untuk menjelaskan pengaruh IPV terhadap suicide ideation pada perempuan korban kekerasan. Intimate partner violence (IPV) adalah segala bentuk kekerasan yang terjadi dalam hubungan romantis yang disebabkan adanya konflik yang tidak terselesaikan dalam hubungan. Suicide Ideation adalah pikiran yang ada di dalam individu mengenai kematian dan respon orang lain terhadap dirinya ketika tidak ada di dunia lagi. Penelitian ini merupakan penelitian kausalitas dengan pendekatan kuantitatif yang melibatkan 81 perempuan sebagai responden. Penelitian ini menggunakan dua alat ukur The Revised Conflict Tactics Scales 2 (CTS2) yang sudah diadaptasi oleh Zahra (2017) dan Adult Suicide Ideation Questionnaire (ASIQ) yang sudah diadaptasi oleh Astuti (2019). Analisis yang digunakan adalah regresi linier sederhana. Nilai koefisiensi regresi sebesar positif 0.421 yang berarti jika terjadi peningkatan variabel IPV maka akan ada terjadi peningkatan suicide ideation. Nilai t hitung > t tabel atau 5.214 > 1.667 artinya terdapat pengaruh yang signifikan antara IPV dan Suicide Ideation.